Management of Urban Amenities in the Context of Public Health Care for Local Communities - Svitlana Kolomiiets; Agnieszka Jakubowska; Eugeniya Goreva (Health Economics and Management Review)
Urbanization is a tendency in the current stage of human development. Numerous public health problems are exacerbated by urbanization, while uncontrolled urbanization can aggravate the current humanitarian crisis and have negative consequences for urban residents' quality of life, health, and safety. The authors highlighted that studying aspects of urbanization's impact on preventing, monitoring, and assessing the urban population morbidity and their quality of life is an urgent task. The study aims to substantiate modern approaches to solving problems of amenity management in the context of local community health based on the analysis of relevant international experience. The methodological part of this study rests on the dialectical method of scientific cognition and a systematic approach. It involved structural and comparative analyses and statistical methods. To gain the study goal, the authors analyzed the peculiarities of urban development management in local community health and examined the relevant EU practices. A comprehensive analysis of urban development in Ukraine was conducted. The obtained results confirmed that the effectiveness of state regulation in the field of amenity of settlements is closely related to the implementation of state policy in this field. Based on the findings, the peculiarities of introducing modern management technologies in the practice of development of city amenities, considering the environmental progress, were determined, and recommendations for their improvement were offered. This study showed that modern strategies and approaches to solving public health problems in cities are related to improving urban planning, urban governance, improving living conditions, and creating equal opportunities for all residents. The authors highlighted that the dissemination of best international practices would allow the implementation of public policy to preserve public health and well-being as one of the most important goals of the community. The study results could be used to develop strategies for increasing the effectiveness of measures to solve problems related to urban development management in the context of local community health.